Visualisasi Pembelajaran Biologi dalam Bentuk Seni Tari Kreasi Sasak pada Materi Pembelahan Sel Tahap Mitosis - Ishak Sirullah; Titi Laily Hajiriah; Agus Muliadi (Biocaster : Jurnal Kajian Biologi, 2026)
Biology learning on the material of mitosis cell division stage is often considered difficult by students, because the concept is abstract and occurs at the microscopic level. Therefore, learning media are needed that are able to visualize the concept in a concrete, interesting, and meaningful way. This study aims to develop visualization of biology learning in the form of Sasak creative dance art on the material of mitosis cell division stage, as well as to determine the feasibility of the media and students' responses to the developed media. This study uses the Research and Development (R&D) method with a simplified Borg & Gall development model. The product was validated by six validators consisting of biologists, dance experts, and Sasak cultural experts, then tested on a limited basis to 30 biology education students who have studied mitosis material using a purposive sampling technique. The results showed that the media obtained a Content Validity Index (CVI) of 0.836 with a valid category, while the average value of Aiken's V in the biology, art, culture, and general aspects, were 0.800; 0.733; 0.933; and 0.878, indicating that the media meets the eligibility criteria for use as a learning medium. Furthermore, students responded positively to the developed media, perceiving it as helpful in understanding the concept of mitosis and potentially increasing learning interest through visual and kinesthetic learning experiences. Therefore, biology learning visualization in the form of Sasak creative dance is suitable for use as an alternative learning medium that integrates biological concepts with local cultural wisdom.